A paradigm shift in use and management of United States public lands for livestock grazing. (1st October 2015) - Hendrickson, Amy Wallop
Abstract: The western United States (US) has been a food-security resource to generate a consistent supply of nutritious, high-protein foods from grazing livestock. Much of the lands in the western US are "public lands" that are administered by US federal land management agencies. Public lands have been historically used to provide multiple ecosystem services that benefit humans, which include food production from grazing livestock. Recent US public land management policies that have been focused specifically on wildlife species-of-interest have resulted in permanent withdrawal of federal public lands from livestock grazing and food production. Decisions to reduce or eliminate grazing on federal public lands reflect a shift from long-standing federal policies designed to ensure a ready supply of domestic food and fiber. Approximately 23% of the US sheep industry is facing imminent loss of grazing access to public lands, which will irretrievably alter the many small-business and family-owned livestock operations and the rural communities that rely on the public lands that surround them. Elimination of livestock grazing removes an effective tool for land managers to maintain range and forest health, enhancing wildlife habitat, controlling invasive weeds, and mitigating wildfire risk.